Pengembangan Sistem Informasi Posyandu Berbasis Website di Bangkinang Kota - Fenty Oktorina; Zulfikar Zulfikar; Andri Nofiar.Am; Nurkholis (Jurnal Sains dan Ilmu Terapan, 2024)
The process of recording children's development at Posyandu Bangkinang Kota is still carried out manually, by writing data on paper without an integrated system to store information and provide schedules for the next Posyandu session. This manual method leads to several issues, such as the risk of damage or loss of development record books due to being stacked with other documents, as well as parents' lack of awareness regarding the upcoming Posyandu schedule. To address these problems, this study develops a web-based Posyandu information system using the PHP programming language, the Laravel framework, and MySQL as the database. The system is designed using Unified Modeling Language (UML) to ensure efficiency in data management. The purpose of this system development is to assist staff in managing children's development information and data more quickly, effectively, and in an organized manner. The research results indicate that the developed information system has been successfully implemented and is capable of addressing issues related to recording and managing children's development data at Posyandu Bangkinang Kota.